Adopted Children's Rights to Inheritance According to Gayo Customary Law and Islamic Inheritance - Nate, Nahara Tawar; Suhartini, Suhartini (Sekolah Tinggi Ilmu Hukum Muhammadiyah Takengon, 2024)
Child adoption in practice often occurs and is a problem that deserves attention, especially in the distribution of inheritance between adoptive parents and adopted children.Â This has become a habit that occurs in society that adopted children are given inheritance rights from their adoptive fathers, even sometimes the relatives of these adoptive fathers are always ignored in obtaining inheritance rights. The purpose of this research is to find out the rights of adopted children to inheritance according to Gayo customary law and Islamic inheritance. This type of research is empirical juridical by using primary data sources and secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials. The data collection method is carried out by interviews and document studies, then it is analyzed qualitatively, so that the reality is found as a symptom of primary data that is linked to theories from secondary data. The data is presented in a descriptive manner, namely by explaining and collecting the problems related to this writing. The results of this research explain that the right of adopted children to inheritance according to Gayo customary law is aligned with biological children and is entitled to inheritance from their adoptive parents. Meanwhile, according to Islamic Law, adopted children obtain inheritance through compulsory wills and adopted children can get more than 1/3 of the inheritance as long as the other heirs have agreed in accordance with Article 183 of the Compilation of Islamic Law.